Scientific Challenges and the Importance of Weather Prediction in Nigeria - Balogun, Ekundayo E. (Obafemi Awolowo University Press, 2013)
A physical scientist involved in a lecture of this type faces two important challenges. The first is how to keep the audience awake and the second is how to express in words ideas that he normally would have expressed by mathematical expressions and equations. How is the understanding and the prediction of weather and climate essentially a problem in Physics? Physics is the science that deals with matter and energy. Physics studies force, motion, heat, light, sound, electricity, magnetism, radiation and atomic structure. Indeed physics is natural philosophy. Meteorology, the science that deals with the question of weather and climate 'is a branch of advanced physics. What is then, the physics behind weather phenomena?